Crooked Run : Poems - Taylor, Henry, 1942- (Book collections on Project MUSE., 2006)
The poems in Crooked Run arise from the landscape, people, and history of a small patch of rural northern Virginia that was once Henry Taylor's home. Taylor moves back and forth over several centuries telling the stories of Loudoun County, part of which is watered by Crooked Run. The stream becomes an emblem of passing time as the poet evokes with love, sometimes with regret, a period and place that modern development has almost obliterated. This is a deeply felt work that in the midst of suburban development summons earlier eras of a locale and its inhabitants with sadness, humor, and a profound sense of loss.